IoT for Future Technology Augmentation: A Radical Approach - Pasupuleti, Mahesh Babu; Miah, Md. Shelim; Adusumalli, Harshini Priya (Engineering International, 2019)
Known as the Internet of Things (IoT), it is a new paradigm that has transformed a traditional way of life into a high-tech way of life. Smart cities, smart homes, pollution management, energy conservation, smart transportation, and smart industries are all examples of transformations brought about by the Internet of Things. A large number of important research studies and investigations have been carried out in order to improve technology through the Internet of Things. However, there is still a slew of obstacles and issues that must be addressed before the Internet of Things can realize its full potential. These challenges and issues must be evaluated from a variety of perspectives related to the Internet of Things, including applications, challenges, enabling technologies, social and environmental implications, and so on. In this review article, the primary purpose is to present an in-depth discussion from both a technological and a sociological standpoint. The article examines the various obstacles and critical issues associated with the Internet of Things and the architecture and important application domains. Additionally, the essay brings to light the existing literature and illustrates its significance to many parts of the Internet of Things. Furthermore, the significance of big data and its analysis in relation to the Internet of Things has been highlighted. This article will assist readers and researchers in better understanding the Internet of Things (IoT) and how it might be applied in the real world.